Effectiveness of Tutors Training Workshop of DYDW Programme at Bangladesh Open University - Sarker, MS Alam; Alam, MS (Journal of Agriculture & Rural Development, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> A three day long training programme of the tutors of Diploma in Youth in Development Work (DYDW) programme was held at Bangladesh Open University (BOU) during March 26-29, 2007 with the aim of upgrading the knowledge, skill, attitude, and quality for better educational exposure of the tutors in pertaining distance education. This evaluation was based on the views and opinion of the participants of the workshop which followed a questionnaire of regarding different parameters like resources personnel, discussed topics, duration of the workshop etc. Out of eighteen participants the highest number of respondents was found to make comment that the training programme was more effective. The participants were highly educated yet the success of the programme would be more if arranged with a training programme with a long duration. The result of the present evaluation demonstrated that the tutors training workshop was very much effective and such type of training workshop is needed at BOU to develop knowledge, skill, attitude, and quality for better performance of the tutors in DYDW Programme through distance mode. Key words: Tutors, training, evaluation, DYDW programme, distance learning. DOI = 10.3329/jard.v5i1.1450 J Agric Rural Dev 5(1&2), 7-12, June 2007